Diagnostic performance of EGFR2, SYPL1, VTN and some biochemical parameters in women with breast cancer: ROC curve analysis and correlation - Mahdi, M. S.; Kadhim, N. Q.; Hussein, H. M. S.; Faris, M. A.; Hasan, S. M.; Khedhir, N. H. (Regulatory Mechanisms in Biosystems, 2026)
Over two million new cases of breast cancer were reported in 2020, making breast cancer the most common cancer among women worldwide. The epidermal growth factor receptor (EGFR) is a vital cell surface receptor involved in cell proliferation and transformation, and its dysregulation is associated with several types of cancer. Synapto phy s in-like protein 1 (SYPL1) is a component of the synapto physin (SYP) family, sometimes referred to as SYPL or panto physin . Vitronectin protein (VTN), also known as S protein or serum dispersion factor, is a vesicular membrane protein found in both neural and non-neural tissues. The study included 90 women aged 30–65 years from Anbar Governorate. They were divided into two groups of 45 women each. The groups consisted of patients diagnosed with breast cancer and healthy women of the same age group as a control group. Serum was isolated and stored at – 20 °C. Quantitative enzyme immunoassay (ELISA) was used to measure EGFR, SYPL1, and VTN levels. The results showed a significant increase in CA 15-3, CA 19-9, VTN, SYPL1 and calcium levels in the breast cancer group compared to the control group. A significant decrease in EGFR2 and magnesium levels was also observed in breast cancer patients compared to the control group. The data showed a strong association between EGFR2, SYPL1, VTN, and breast cancer. The ROC curve results indicate that SYPL1 is the most effe c tive in detecting breast cancer. Based on these findings, it is suggested that circulating EGFR2, SYPL1, and VTN concentrations can be used to monitor treatment and predict breast cancer.